Solar energy power (source) / Mohamad Shahrun Azizan and Mohd Azizul Mat Ariff - Azizan, Mohamad Shahrun; Mat Ariff, Mohd Azizul (2005)
You've probably seen calculators that have solar cells — calculators that never need batteries, and in some cases don't even have an off button. As long as you have enough light, they seem to work forever. You may have seen larger solar panels — on emergency road signs or call boxes, on buoys, even in parking lots to power lights. Although these larger panels aren't as common as solar powered calculators, they're out there and not that hard to spot if you know where to look. There are solar cell arrays on satellites, where they are used to power the electrical systems. You have probably also been hearing about the "solar revolution" for the last 20 years -- the idea that one day we will all use free electricity from the sun. This is a seductive promise: On a bright, sunny day, the sun shines approximately 1,000 watts of energy per square meter of the planet's surface, and if we could collect all of that energy w e could easily power our homes and offices for free. In this project, we will examine solar cells to learn how they convert the sun's energy directly into electricity. In the process, you will learn why we are getting closer to using the sun's energy on a daily basis, and why we still have more research to do before the process becomes cost effective